2013
DOI: 10.1002/qre.1573
|View full text |Cite
|
Sign up to set email alerts
|

Improved Exponentially Weighted Moving Average Control Charts for Monitoring Process Mean and Dispersion

Abstract: Exponentially weighted moving average (EWMA) control charts are mostly used to monitor the manufacturing processes. In this paper, we propose some improved EWMA control charts for detecting the random shifts in the process mean and process dispersion. These EWMA control charts are based on the best linear unbiased estimators obtained under ordered ranked set sampling (ORSS) and ordered imperfect ranked set sampling (OIRSS), named EWMA‐ORSS and EWMA‐OIRSS charts, respectively. Monte Carlo simulations are used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 54 publications
0
41
0
1
Order By: Relevance
“…We combine the whole data set to have 200‐inside‐diameter measurements of piston rings. It is shown in Haq et al that the data set reasonably satisfies the normality assumption. From 200 measurements, 30 samples, each of size five, are selected using SRS, RSS, and PRSS schemes.…”
Section: An Application To Real Datamentioning
confidence: 90%
See 1 more Smart Citation
“…We combine the whole data set to have 200‐inside‐diameter measurements of piston rings. It is shown in Haq et al that the data set reasonably satisfies the normality assumption. From 200 measurements, 30 samples, each of size five, are selected using SRS, RSS, and PRSS schemes.…”
Section: An Application To Real Datamentioning
confidence: 90%
“…They showed that the RSS‐based mean charts are more powerful than the Shewhart mean chart based on SRS. For more details about the control charts based on different RSS schemes, refer to Abujiya and Muttlak, Abujiya et al , Abujiya et al , Al‐Omari and Haq, Mehmood, Haq, Haq et al , Haq et al , and the references cited therein.…”
Section: Introductionmentioning
confidence: 99%
“…Haq et al . developed improved EWMA control charts based on the BLUEs‐ORSS and showed that these control charts are able to perform better than the EWMA control charts based on SRS and RSS schemes. Later on, Haq et al .…”
Section: Introductionmentioning
confidence: 99%
“…G}B w [2] CQ@= Q \UwD 3 |atHD`tH pQDvm Q=Owtv w 2 |}=tv uwRwt Q=Owtv wO u}= R= OW=@ Q_v Ot Ov}=Qi QO lJwm C= Q}}eD x@ uOQ@|B xm|v=tR "CU= |=yxYNWt uOw@Q}eDt ZQi =@ =yQ=Owtv u}= |x}rw= |L=Q] "OwW|t xO=iDU= pQDvm QO |Q}osWJ |=yCiQW}B w =yOw@y@ Q}N= |=yp=U QO "CU= xOW s=Hv= |i}m |atHD`tH pQDvm w |}=tv uwRwt lQLDt u}ov=}t pQDvm Q=Owtv wO Qy Q=DN=U CQwY =yOv}=Qi QO C=i= QLv= X}NWD QO pQDvm |=yQ=Owtv u}= |}=Q=m V}=Ri= Qw_vtx@ |@}mQD pQDvm Q=Owtv R= xO=iDU= =@ = Q |O}OH pQDvm Q=Owtv [4] T=mwr "CU= xDiQo pQDvm Q=Owtv pQDvm OwOL R= Q=Owtv u}= QO [20] [6] Q} RwQm w T=mwr \UwD 4`} QU |x}rw= MU=B =@ |atHD = Q`}QU x}rw= MU=B =@ |}=tv uwRwt lQLDt u}ov=}t pQDvm Q=Owtv [7] Qv}=DW= x@=Wt u}= QO w= 'OQm O=yvW}B = Q 5 |vRw |atHD`tH pQDvm Q=Owtv [8] u}JU=} "OQm x=Q= "O=O X=YDN= uRw |atHD`tH pQDvm Q=Owtv |=yxQ=t; |xDWPo C=aq]= x@ Q=Owtv 6 xQ}eDtOvJ |}=tv uwRwt lQLDt u}ov=}t |xDi=}s}taD pQDvm Q=Owtv [9] wq w utQOv}r u=tRsy Qw]x@ O}=@ QDt=Q=B l} R= V}@ |Dkw xQ}eDtOvJ |=yOv}= Qi V}=B |= Q@ = Q |=yQ=Owtv R= |}xDi=}s}taD pOt [10] [12] u= Q=mty w Z=}Q "OvwW|t w T=@a "OvOQm xO=iDU= nQR@ w lJwm C= Q}}eD |= Q@ |atHD`tH pQDvm Q=Owtv R= xO=iDU= =@ = Q |}=tv uwRwt lQLDt u}ov=}t pQDvm Q=Owtv OQmrta [13] u= Q=mty R= xO=iDU= =@ [14] …”
mentioning
confidence: 99%
“…w MEC OwHwt l}Uqm |@}mQD pQDvm |=yQ=Owtv "3 (20) |=yxQ=t;C + RSS;t ; C RSS;t "CU=MCE-RSSpQDvmQ=Owtv|R=UQ=wtyQDt= Q=Bc "OvDUy CUSUM-RSS pQDvm Q=Owtv …”
unclassified